Gene Expression Analysis of Lung Adenocarcinoma and Matched Adjacent Non-tumor Lung Tissue. Issue 3 (May 2014) - Zhang, Wenmei; Gong, Wei; Ai, Hua; Tang, Jie; Shen, Ce
Aims and Background: The aim of this study was to find disease-associated genes and gene functions in lung adenocarcinoma and matched adjacent non-tumor lung tissues with DNA microarray. Methods: We downloaded the gene expression profile GSE32863 from the Gene Expression Omnibus database including 58 lung adenocarcinoma and 58 adjacent nontumor lung tissue samples. Data were preprocessed and the differentially expressed genes (DEGs) were identified using packages in the R computing language. The selected DEGs were further analyzed with bioinformatics methods. After the coexpression network of DEGs was constructed by STRING (Search Tool for the Retrieval of Interacting Genes/Proteins), we analyzed gene functions with DAVID (The Database for Annotation, Visualization and Integrated Discovery) and WebGestalt (WEB-based Gene Set Analysis Toolkit). Results: A total of 1429 genes were filtered as DEGs, including 873 downregulated genes and 556 upregulated genes, and the DEGs including CDC45, CCNB2, CDC20, MCM2, PTTG1, MCM4 and FEN1 were most significantly related to cell cycle and DNA replication. Conclusion: The discovery of featured genes which were significantly related to cell cycle and DNA replication has potential for use in the clinic for the diagnosis of lung adenocarcinoma in the future. However, further experiments will be needed to confirm our result.